Prospective clinical trial on the effectiveness of Topical Anesthetic in second stage surgeries of Dental Implants - Jordi Ortega-Martínez; Elvira Ferrés-Amat; Eduard Ferrés-Padró; Federico Hernández-Alfaro (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Objectives: The aim of this study is to evaluate the effectiveness of gel topical anaesthesia in second surgeries of dental implants according to the different treated areas of the oral cavity, as well as the type of oral mucosa in which is effective. Material and methods: Thirteen partially and completely edentulous patients with 30 implants in total were included in the study. The oral mucosa was dried and the anesthetic gel (Benzocaine 20%) was applied with a cotton roll for 2 minutes. The effectiveness was evaluated with an exploratory probe. Those implants whose cover screw was not submerged in a depth higher than 2-4 mm were selected. In the event of the gel topical anaesthesia not being effective, reinforcement with conventional infiltrative anaesthesia was made. Pain was measured with Visual Analogue Scales (VAS), and the gum thickness with periodontal probe. A one-way Anova and a Pearson correlation were used to perform the statistical analysis (p≤0.05). Results: The 66.67% of the sample needed reinforcement through conventional anesthetic infiltration. No statistically signifi cant differences were found in the comparison of pain with different gum thickness (p=0.59), although a higher feeling of pain was actually observed in those patients who were firstly subjected to a second-stage surgery (p=0.0335). Conclusion: The use of gel topical anaesthesia cannot be considered as the sole treatment to eliminate the feeling of pain, but as a coadjuvant to infiltrative anesthesia. No significant differences have been found between the different treated areas of the oral cavity, nor in the thickness or type of oral mucosa.